Επιπτώσεις της επιλόχειας κατάθλιψης στο παιδί - Έλενα, Ευαγόρου (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: Postnatal depression is a serious health problem that affects one in seven women during the first months after childbirth. Many studies have reported that postnatal depression has had harmful effects on the physical, cognitive and emotional development of children. Aim: The aim of this project was to investigate if postnatal depression in mothers can be linked to any problems in child development. Research and Methods: The method that was used was a critical review of relevant research literature. Greek and international sources were found through search engines (PubMed, Google Scholar and Cinahl) by using the keywords: “child development and maternal postnatal depression”, “child cognitive development and postpartum depression”, “child behaviour problems and postpartum depression and postnatal depression”. The final investigation included 8 research studies. Results: This research process indicates that postnatal depression negatively effects child development. The results of the sources vary and there are multiple factors that change the effects. It has been found that boys are more prone to the effects of postnatal depression and have delays in physical and cognitive development, whereas girls present increased aggression and hyperactivity. Furthermore it is shown that these problems can be eliminated with an early diagnosis of postnatal depression. Conclusion: Postnatal depression afflicts both mothers as well as their children. Mothers battling postnatal depression can be helped by the psychological support provided by close family members and healthcare professionals.
Keywords: Postpartum depression; Anxiety in women; Depression, Postpartum; Postpartum Period--psychology; Child development